The The Influence Of Consumer Psychology And Electronıc Word Of Mouth On Purchase Decısıons Of Elden Rıng Steam Vıdeo Games In Indonesıa - Makmun Riyanto; Fadhli Insan Al Arif; Rif'ah Dwi Astuti; Umar Farouk; Sugiyanta Sugiyanta (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study plans to decide the impact of Shopper Brain science (X1) and Electronic Verbal (X2) on Elden Ring Steam computer games Buy Choices (Y) in Indonesia. The respondents of this exploration are Elden Rings Steam PC games customers in Indonesia. Tests were taken by utilizing purposive examining of 100 respondents. Information assortment was finished by perception, surveys, and writing study. Strategies for information examination utilized were legitimacy test, dependability test, three box strategy test, exemplary presumption test, numerous direct relapse investigation, F test, coefficient of assurance, and t test. From the calculation of the index value with the three box method test, it is known that all variables are in the high category, meaning that the respondents' perceptions of the Consumer Psychology variable (which has four indicators of motivation, perception, attitude, learning) and respondents' perceptions of the Electronic Word of Mouth variable (which consists of three indicators: Intensity, Valence of Opinion, Content) is high or good Based on the results of data processing, the regression equation Y = 10.860 + 0.644X1 + 0.463X2 is obtained. From the results of the F test, it was obtained that F count was greater than F table Likewise with the results of the t test, all variables in this study t count was greater than t table and had a significance value of less than 0.05, so it could be concluded that all variables, namely psychological variables Consumers and Electronic Word Of Mouth have a significant effect on Purchasing Decisions. Companies can increase the Consumer Psychology variable (by increasing consumers' positive perceptions and attitudes toward the Elden Ring video game, increasing consumer learning factors, namely increasing consumers' desire to learn/try, and increasing consumers' motivation to own and play Elden Ring video game) and the Electronic word of mouth variable (by increasing consumers' intensity to access the Elden Ring Steam social media application, increasing consumers' positive Valence of Opinion by encouraging consumers (gamers) to make positive recommendations) in order to increase the purchase decision for the Elden Ring.